Powder Intrinsic Properties as Dustiness Predictor for an Efficient Exposure Assessment?. Issue 9 (6th October 2019) - Shandilya, Neeraj; Kuijpers, Eelco; Tuinman, Ilse; Fransman, Wouter
Abstract: Dustiness is not an intrinsic physically defined property of a powder, but the tendency of particles to become airborne in response to mechanical and/or aerodynamic stimuli. The present study considers a set of 10 physical properties to which the powder dustiness can be attributed. Through a preliminary investigation of a standardized continuous drop test scenario, we present first set of results on the varying degrees or weights of influence of these properties on the aerosolization tendency of powder particles. The inter-particle distance is found to be the most dominant property controlling the particle aerosolization, followed by the ability of powder particles to get electrostatically charged. We observe the kinetics involved during powder aerosolization to be governed by two ratios: drag force/cohesive force and drag force/gravitational force. The converging tendencies in these initial results indicate that these physical properties can be used to model dustiness of falling powder, which can eventually be used in risk assessment tools for an efficient exposure estimation of the powders.